The analysis of science literacy knowledge aspects of high school students on the concepts of heat and temperature - W D Rahayu; J Maknun; D Mulhayatiah; P Dimas (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
Scientific literacy is one of the skills needed in today's digital era so that the ability of the 21st century can be achieved. Science literacy students aspects of knowledge on the topic of heat and temperature physics in high school being the purpose of this research. Science literacy that is used is the result of the adaptation of the PISA year 2015. Research in the form of analysis of science literacy of students in one high school in Bandung has 6 class XII which populations, and taking 1 class as a randomly selected sample. Data collection techniques derived from assessment question of temperature and the heat that has been validated and interviews using interview guidelines. The results showed that the ability of high school students in science literacy is still low with the percentage of each indicator in the aspect of knowledge, 63.45%, Procedural content 73,79% m and epistemic 43.45% if averaged became 60.23%. Science literacy requires increased lace through science literacy trained learning or to develop instruments that can trained the science literacy of the students.